A comparison of functional analysis methods of inappropriate mealtime behavior. Issue 3 (26th March 2019) - Bachmeyer, Melanie H.; Kirkwood, Caitlin A.; Criscito, Amanda B.; Mauzy, Courtney R.; Berth, Diane P.
Abstract : Investigators have evaluated two procedural variations for conducting a functional analysis of inappropriate mealtime behavior exhibited by children with feeding problems. One method involves prompting bites only in the escape condition (e.g., Najdowski et al., 2008). Another method involves prompting bites across all conditions (e.g., Piazza et al., 2003). We assessed the food refusal of 3 children diagnosed with a feeding disorder by comparing the two variations. The two methods resulted in different outcomes for 2 of 3 children. Prompting bites only in the escape condition identified a single function (i.e., escape). Prompting bites across all conditions identified multiple functions (i.e., escape and attention). We then examined the relative effects of extinction procedures (individually and in combination) to determine the validity of each method. Results of the treatment evaluation suggested that the procedural variation that failed to identify an attention function for 2 of 3 children produced false negative findings.